Halveti-Şâbânî Şeyhi Mustafa Kemâleddîn Bekrî ve Hediyyetü’l-Ahbâb Adlı Eseri / Khalvati-Shabani Sheikh Mustapha Kamaladdin Bakri and his Work Hadiyyat al-Ahbab - Gül, Halim (Journal of History Culture and Art Research, 2013)
Abstract This article studies the life and woks of Kemaleddin Bekrî, who affiliated himself to Khalvati-Shabani Sheikh Abdullatîf b. Hüsameddîn el-Halebî, and who was growed up under Abd al-Ghani al-Nabulsi’s control. His work Hadiyyat al-Ahbab fi ma li’l-Khalveti min al-Şuruti va’l-Adab, which explains the conditions and rules of khalvet was also studied. The work consists of preface, eight parts and an epilogue and all parts examined in detail. Öz Bu makalede, Abdülganî Nablusî’nin (ö.1143/1730) gözetiminde yetişen, halvetî-Şabânî şeyhi Abdullatîf b. Hüsameddîn el-Halebî’ye intisap eden Mustafa Kemaleddin Bekrî’nin hayatı ve eserleri incelenmiştir. Bu çerçevede onun tasavvufi bir kavram olan halvetin âdab ve şartlarını izah eden Hediyyetü’l ahbâb fî mâ li’l-halveti mine’ş-şurûti ve’l-âdâb adlı risalesinin incelenmesi ve değerlendirmesi üzerinde durulmuştur. Söz konusu eser, mukaddime sekiz bölüm ve bir hatimeden oluşmaktadır. Le Shaykh Khalwatî-Sha’bânî Mustafâ Kamâl al-Dîn Bakrî et son Traité qui s’intitule Hadiyya al-ahbâb Résumé Dans cet article, on va étudier d’abord la vie et les œuvres du Shaykh Khalwatî-Sha’bânî Mustafâ Kamâl al-Dîn Bakrî qui a été éduqué par le célèbre soufi ’Abd al-Ghanî Nablûsî (m. 1143/1730) et a été initié par ’Abd al-Latîf b. Husâm al-Dîn al-Halabî. Puis, plus particulièrement, on va analyser son traité qui s’intitule ’Hadiyya al-ahbâb fî mâ li’l-khalwatî min al-shurût wa’l-âdâb’. Ce traité qui a été composé de dix-huit chapitres et d’une conclusion étudie les convenances et les conditions de la retraite spirituelle, khalwa, une des notions soufies importantes.